Evaluasi Implementasi UU No. 11 Tahun 2012 tentang Sistem Peradilan Pidana Anak dalam Kasus Psikotropika - Herlambang, Arsyi Murdianto; Rustam, Muhammad Rizal (Decisio: Jurnal Ilmiah Hukum, 2024)
Children involved in psychotropic offenses require special attention in the criminal justice system due to their psychological and developmental vulnerability. The Indonesian government enacted Law No. 11 of 2012 on the Juvenile Criminal Justice System (SPPA) to emphasize diversion and restorative justice as primary approaches in handling juvenile offenders. However, the implementation of this law in psychotropic cases remains problematic due to legal inconsistencies, institutional limitations, and societal stigma. This study evaluates the effectiveness of SPPA in addressing juvenile psychotropic offenses and identifies the key challenges in its enforcement.This research employs a qualitative methodology with a normative juridical approach, focusing on regulatory analysis and legal norm interpretation. Data collection is conducted through an extensive literature review, incorporating primary and secondary legal sources to provide a comprehensive understanding of the law's practical application.The findings indicate that while the SPPA theoretically promotes a rehabilitative and restorative approach, its application in psychotropic offenses remains inconsistent. Legal constraints, including the lack of synchronization between the SPPA and its implementing regulations, have hindered the optimal execution of diversion. Institutional challenges, such as limited rehabilitation facilities and lack of trained professionals, exacerbate the issue, often leading to punitive measures against juvenile offenders. Moreover, strong social stigma further obstructs reintegration efforts, necessitating policy reform, legal harmonization, and enhanced community awareness to ensure effective juvenile justice implementation.